(3eNJUQ GdefJXe dGHf GdLhRis - (3Ydj GdSWGeis; (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL,J (B597 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ChOY ai Yde GdJGQjN CSQGQ ef YQagG CJi OGQ GdSYGOI ef HGHgG CeG HYO ajbhd (B: (3deG hbY fXQi ai OGQ GdSdWfI Ydi cJGH GdefJXe aGNJUQJg s
(3BNQgG (B:s
(3BNQ GdehLhO efg LGAJ NhdI HfJ Mcje abGdJ (B: (3jG QShd Gddg GdGJJRhL bGd ef bGdJ Cf TFJ HcQ Ch Ef TFJ KjHkG abGdJ jG Ce QheGf eGPG CONd Gddg Ydjce ef GdNjQ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1851s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs